m276-SL-PBD eradicates tumors and instigates long-lasting tumor-free survival in Merkel cell carcinoma preclinical models - Mikaela D. Kunika; Aarthi Kannan; Graham J. Velasco; Yang Feng; Steven Seaman; Bhaba K. Das; Dillon Pham; Nils Lambrecht; Haibo Zhao; Brad St. Croix; Ling Gao (iScience)
Summary: Merkel cell carcinoma (MCC) is a rare but aggressive neuroendocrine carcinoma, and immune checkpoint inhibitors (ICIs) are the only approved therapy; nonetheless, resistance is notable and there is a critical need for novel effective therapies. Recently, CD276 was identified as a promising therapeutic target in human cancers. In preclinical studies, a modified CD276 antibody-drug conjugate (ADC) with pyrrolobenzodiazepine (m276-SL-PBD) elicited more potent anti-tumor effects than two CD276 ADCs currently in clinical trials. Here, we uncover notable CD276 expression in MCC patient tumors, and demonstrate m276-SL-PBD efficacy against MCC preclinical models. Complete eradication is observed in all xenografts bearing CD276 expression, with 82% achieving 180-day tumor-free survival after 4 or 5 weekly doses, and m276-SL-PBD remained efficacious against relapsed tumors. Of clinical relevance, m276-SL-PBD retains its potency in MCC-bearing humanized mice. Importantly, no detectable adverse effects were observed. Thus, m276-SL-PBD is a promising therapy for patients unsuitable or resistant to ICIs.